Foraging and anti-predation behavior of Thomson’s gazelles (Gazella thomsoni) and Grant’s gazelles (Gazella granti) at a waterhole - Rautiainen, Heidi (SLU/Dept. of Animal Environment and Health (until 231231), 2014)
Prey species make behavioral decisions to reduce the perceived risk of predation and the time spent vulnerable to predation. Behavioral responses to predators are for example selection of specific habitat types and the presence of predators influence individual vigilance. Furthermore, there is a variation in feeding niches with different herbivores focusing their foraging effort on different vegetation types which is also expected to affect the choice of habitat. Behavioral data on anti-predation and foraging behavior at on waterhole is collected from Thomson’s and Grant’s gazelles at Ol Pejeta Conservancy (0°00’N, 36°56’E) located in semiarid bushed grassland in Laikipia district of central Kenya. The main predators at the waterhole are lions, black-backed jackals, spotted hyenas, cheetahs and African wild dogs. Direct observations were carried out from a car 250 meters from the waterhole. Observations were carried out daytime by scan sampling from sunrise to sunset in February 2014. The aim of this study was to design and test a study that investigates how Thomson’s and Grant’s gazelles differ in foraging and anti-predation behavior during daytime close to a waterhole. The results show that the number and visiting frequency of Thomson’s gazelles was higher at the study area than Grant’s gazelles and the number of Thomson’s gazelles was higher in the morning than in the afternoon. Because of low amount of Grant’s gazelles, no further analysis on this species was made. Based on results or when not possible by literature, Thomson’s and Grant’s gazelles seem to differ in anti-predation and foraging behavior by differences in habitat preferences, water dependency, group size and physical characteristics.